Progress in the Application of Peptide Vaccines in the COVID-19 - Zhang, Mengxue (Transactions on Materials, Biotechnology and Life Sciences, 2024)
A brand-new coronavirus dubbed COVID-19 epidemic broke out in the winter of 2019 and quickly swept the globe. Additionally, the pandemic's high mortality rate and high infection have prompted sustained scientific efforts to treat the illness. Backing the history of the virus, vaccine development is the most effective method to mitigate this urgent public issue. Pharmaceutical firms from nations including China, the United States, and Russia subsequently started doing research on vaccine development. While Pfizer and Monard in the US utilize mRNA genetic vaccines, China uses inactivated vaccines and viral vector vaccines. As a result of the difficult inactivated vaccine manufacture procedure and the issue of toxicity rebound, there is also a chance that genetic vaccines will mate with host genes. It is thought that the creation of peptide vaccines will deal with these two problems. Peptide vaccines are therefore seen to be the safest, and they may be employed not only for preventative immunization but also for the treatment of solid malignancies. Clinical studies for peptide vaccines are underway. But because peptide vaccinations are quickly broken down by cells, their drug carriers play a crucial role as well. This article will outline the selection of the protein sequence for the COVID-19 peptide vaccine as well as the development of its tests.